STRATEGIES FOR PRESERVING AND STRENGTHENING FAMILY VALUES IN THE ERA OF INFORMATION THREATS, PSYCHOLOGICAL FEATURES OF PERSONALITY FORMATION IN ADOLESCENCE. (Universal International Scientific Journal, 2026)
This thesis examines the psychological characteristics of personalitydevelopment during adolescence. The study analyzes adolescents’ internal motivation, selfawareness, decision-making abilities, and social adaptation processes. The role of family, school,and peer groups in shaping adolescent development is highlighted. The results indicate that asupportive family atmosphere and engaged educational guidance play a key role in helpingadolescents develop into resilient and socially skilled individuals.
Keywords: adolescence; personality formation; psychological characteristics